A composição química da goiabeira (Psidium guajava L.) - Sobr, M. O. C. do Brasil; Mello, F. A. F. de; Haag, H. P.; Leme Jr., J. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1961)
This paper deals with the mineral composition fresh and dry matter production of different organs of 4, 5 old guava (Psidium guajava L.) growth on sandy soil (Savanna) without fertilizer. The data obtained for fresh and dry matter productior are present in table 2 (in Portuguese). The concentration of the elements are presented in table 3 (in Portuguese). Finally, the total amounts of elements absorbed by guava are given in the following table: Element Plant (grams) Fruits (grams) Nitrogen (N) 42,55 20,4 Phosphorus (P) 3,84 2,3 Potassium (K) 52,01 31,3 Calcium (Ca) 47,81 0,2 Magnesium (Mg) 2,4